Bahasa Inggris - Herdiman, Lobes; Susy Susmartini; Sukma Yustika Andriani (JST (Jurnal Sains dan Teknologi), 2024)
The investigation stimulates toddlers to learn to walk using a baby walker (BW), allowing the toddler's soles to land on the floor surface. This research compares the effectiveness of using BWstandard and Redesign in stimulating toddlers to learn to walk with Kinect Sensor and Force Sensing Resistor (FSR) devices using video-based biomechanics. This research involved 9 toddlers; the minimum age of toddlers was 9 months, body length 70-80cm, and foot length 10-12cm. The biomechanics of toddlers on leg compression are performed via video in real-time using Kinect Sensor with movement analysis developed through Microsoft Visual Studio Software and Vitruvius Software. Measuring foot pressure using FSR is connected to the Arduino IDE system and placed in the prewalker sock via 5 reading points. Statistical tests use paired sample t-tests. Toddler foot compression force using BWstandard (Redesign), heel-strike phase 218.98 N (447.66 N), midstance phase 273.08 N (462.61 N), toe-off phase 181.94 N (371.99 N), and foot pressure 248 N (339 N). The results of the Pair sample t-test showed that there was a difference in use between BWstandard and Redesign. It was concluded that stimulation of toddlers learning to walk was achieved more effectively using BWredesign and was more recommended.